MUSYAWARAH PERSPEKTIF FILSAFAT EKONOMI ISLAM - Atok Syihabuddin (Maliyah : Jurnal Hukum Bisnis Islam, 2018)
This paper is an explorative literature study. The author explores the value of mushawarah directed to Islamic economics. Islam is very high attention to mushawarah. Even in the Qur'an there is a verse that commands deliberations for all matters so that the sura is called surah al-syura (mushawarah). The author wants to see the position of deliberation from the point of view of philosophy, both from the side of ontology, epistemology, and axiology. The study of mushawarah on the ontological side can be presented by presenting various Qur'anic and Hadith texts related to musyawarah. Assessing mushawarah at the epistemology level means connecting the concept of deliberation into one of the sciences. The author tries to pull it into the economic discussion. While in the level of axiology is the study of mushawarah applied in economic activities, namely, review of the contract on the practical level.